Analisis Efektivitas Dan Kontribusi Pajak Daerah Terhadap Pendapatan Asli Daerah Provinsi Lampung - Kurnia, Azizah Dwi; Gunarto, Toto (CV. ITTC INDONESIA, 2024)
Delegation of authority to regional governments through regional autonomy requires maximization of tax effectiveness and regional tax contributions as the largest source of PAD revenue. Lampung Province as the gateway to Sumatra Island provides the advantage to be able to maximize regional potential and regional development through the effectiveness and contribution of taxes to PAD. This research aims to determine the effectiveness of regional tax revenue, and the contribution of regional tax sectors to PAD in Lampung Province in 2021 and 2022 using quantitative descriptive methods. The research results show that the effectiveness of taxes in 15 regencies/cities in Lampung province fluctuates, and the largest contribution from the regional tax sector was street lighting tax.